2002
DOI: 10.1093/jxb/erf083
|View full text |Cite
|
Sign up to set email alerts
|

Use of infrared thermography for monitoring stomatal closure in the field: application to grapevine

Abstract: This paper reviews and discusses strategies for the use of thermal imaging for studies of stomatal conductance in the field and compares techniques for image collection and analysis. Measurements were taken under a range of environmental conditions and on sunlit and shaded canopies to illustrate the variability of temperatures and derived stress indices. A simple procedure is presented for correcting for calibration drift within the images from the low-cost thermal imager used (SnapShot 225, Infrared Solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
366
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(388 citation statements)
references
References 20 publications
15
366
0
7
Order By: Relevance
“…There are numerous comprehensive reviews on plant-water relations (e.g. Slayter 1967;Lösch 1995;Kramer and Boyer 1995;Kirkham 2005;Jones et al 2008;Nobel 2009;Passioura 2010;Asbjornsen et al 2011). Here, we only give a short overview of main properties and processes as a basis to understand the relevant traits in crop stress response that might be targeted by management under different hydrological conditions.…”
Section: Plant Subsystemmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous comprehensive reviews on plant-water relations (e.g. Slayter 1967;Lösch 1995;Kramer and Boyer 1995;Kirkham 2005;Jones et al 2008;Nobel 2009;Passioura 2010;Asbjornsen et al 2011). Here, we only give a short overview of main properties and processes as a basis to understand the relevant traits in crop stress response that might be targeted by management under different hydrological conditions.…”
Section: Plant Subsystemmentioning
confidence: 99%
“…The microclimate within a crop stand essentially determines the amount of vapour transfer via the leaf boundary layer resistance and the overall water potential gradient driving the flux through the SPAC (Jones 1992;Monteith 1995). Depending on canopy architecture, several meteorological variables such as radiation, CO 2 concentration, temperature, humidity and wind speed differ within a crop stand from the surrounding atmosphere.…”
Section: Subsystem Interactions and Feedbacksmentioning
confidence: 99%
“…Measurements of PRI in the canopy of leaves (from single plant or group of plants) can be also based on the application of spectrometers or multispectral and hyperspectral cameras [15,61], which can be placed on a mobile platform (e.g., drone) or fixed at a certain distance from the canopy [35,38]. Photosynthetic parameters in leaves (in particular, ∆F/Fm', NPQ, and LUE) can be measured by standard methods, including PAM-fluorometry [16,17] and analysis of CO 2 exchange [21][22][23][24][25]. However, the application of these methods on the canopy level is a very difficult problem.…”
Section: Main Principles Of Data Analysismentioning
confidence: 99%
“…As a result, remote sensing of the photosynthetic process is an important practical problem [13][14][15]. There are many methods that can be used for the analysis of the photosynthesis process in plants; in particular, pulse-amplitude-modulation (PAM)-fluorometry [16,17], JIP-test [18][19][20], and analysis of CO 2 exchange [21][22][23][24][25]. These methods are very effective in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Stress indices have been proposed (JACKSON; REGINATO; CLAWSON;BLAD, 1982;IDSO et al, 1981;JACKSON et al, 1981;MORAN et al, 1994), directly or empirically related to stomatal conductance which is the key physiological parameter linked to plant water status. More recently, several studies have been reported on the use of infrared thermometry and thermal images to directly estimate stomatal resistance to water vapor flux (JONES, 1999;JONES et al, 2002;LEINONEN et al, 2006). Idso, Jackson and Reginato (1977) and Jackson, Reginato and Idso (1977) included the temperature difference between canopy (measured with infrared thermometers) and air in an index of plant water status, the Stress-Degree-Index.…”
Section: Detection Of Plant Water Stress By Infrared Thermometrymentioning
confidence: 99%